Games to improve strength endurance in the municipality judokas of Pinar del Río - Osviel Hernández Sotolongo; Ramón Martínez Vidal (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The sport judo has been one of those that more satisfactions have caused in the national competitions and according to statistical most of the excellent athletes in this sport have been formed in the county Pinegrove of the River, however in the last years it has been come manifesting a fall in the competitive results in the category 11-12 years of this municipality. It is for it that is carried out this work, which has as objective to elaborate a proposal of games for the development from the resistance to the force in the judo athletes, category 11-12 years of the municipality Pinegrove of the River, keeping in mind that in these ages the boy feels more motivation for the game than for the exercises, which are more rigid and in many cases they become monotonous for them. For the realization of the investigation theoretical and empiric methods were used as the documental analysis, the Observation and the interview. As a result it is provided the trainers a bibliographical material of consultations for the one which to be aided for the work from the resistance to the force in judo athletes, from early ages, which constitute the fundamental pyramid of the system of the high Cuban sport yield.